(3GdSjGSI GdLfGFjI decGaMI LQjeI ZSd GdCehGd (B: s (3OQGSI ebGQfI (B/ s - (3eLOi eMeO YHOGdQMje CMeOs; (3eMehO cHjT s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3jeKd ZSd GdCehGd XGgQI ELQGejI JgOO GdGbJUGO ai eYXe Ohd GdYGde h Pdc HYO Cf HQR OhQ GdELQGe GdefXe aj YQbdI ELQGAGJ JYbH h VHW h eUGOQI GdCehGd ZjQ GdeTQhYI(B: (3h aj JYRjR GdCfTWI GdELQGejI h GdGSJNOGe ZjQ GdeTQhY ddfXe GdeUQajI(B: (3aVdkG Yf fTQ GdaSGO heMGhdI GSJZdGd GdCehGd eMd GdZSd ai CfTWI ELQGejI CNQi(B. (3h deG JbOe aEf efgL GdHMK aj gPg GdOQGSI cGf bhGeg JMdjd h OQGSI LejY GdeSGFd GdJTQjYjI PGJ GdUdI HLQjeI ZSd GdCehGd ShGA CcGfJ JKjQ eTGcd YedjI aj EfaGP GdbGfhf ef GdfGMjI GdehVhYjI Ce ef GdfGMjI GdELQGFjI(B. (3h cGf Pdc ef NdGd GSJbQGA GdJTQjYGJ GdebGQfI hUhdkG dhVY Mdhd YedjI(B: (3h JOGQc Ci fbU ai Cj fUhU bGFeI h MSe Cj NdGa jKhQ aj JWHjb gPg GdfUhU(B. (3h jgOa gPG cdg Edi hVY JUhQ dJYOjd JTQjYj h MdhdkG YedjI deLGHgI gPg GdLQjeI(B. (3h gh eG MOG HfG ddMOjK HOGjI Yf GdehGLgI GdLfGFjI ddLQjeI ef GdfGMjI GdehVhYjI NdGd KdGKI aUhd(B: (3jJMOK ChdgG aj eHMKjf Yf GdBKGQ GdGbJUGOjI dYedjGJ ZSd GdCehGd ZjQ GdeTQhYI h Yf GdeUdMI GdeMejI GdJi jQGYjgG GdbGfhf eMd GdOQGSI(B. (3Ke JMOKfG aj KGfj gPg GdaUhd Yf CQcGf GdLQjeI aj KdGKI eHGMK Ydi GdJQJjH h gj GdLQjeI GdChdjI Ch eG jYQa abgkG HGdLQjeI GdeUOQ(B: (3h GdMOjK NGUI Yf GdGJLGg GdeDjO dJMOjO gPg GdLQjeI HGdCSdhH GdMUQi(B: (3h GdfbO GdehLg dgPG GdGJLGg h YOhd GdeTQY GdeUQi eDNQkG Yf GdGNP HgPG GdCSdhHs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B305-312s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3LQjeI ZSd GdGehGds; (3GdGKGQ GdGbJUGOjI dYedjGJ ZSd GdGehGds; (3GQcGf LQjeI ZSd GdGehGds; (3YbhHGJ LQjeI ZSd GdGehGds; (3GdehGLgI GdLfGFjI dLQjeI ZSd GdGehGds; (3GdJYGhf GdOhdj GdGLQGFj aj ecGaMI ZSd GdGehGds; (3GdGJaGbjGJ GdOhdjI aj eLGd ecGaMI ZSd GdGehGds; (3GdeUdMI eMd GdMeGjI GdLfGFjI aj LQjeI ZSd GdGehGds; (3JSdje GdeLQejf aj LQjeI ZSd GdGehGds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs